Segmentation of speech on phonetic elements for systems of speech information protection - Y. N. Seitkulov; S. N. Boranbayev; A. V. Patapovich; H. V. Davydau (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article is devoted to the development of speech segmentation algorithm on phonetic elements for the synthesis of speech-like signals in speech information protection systems. The main attention is paid to establishing the boundaries of phonetic units of speech, taking into account the influence of this factor on the quality of the synthesized speech by the compilation method. The features of establishing the boundaries of phonemes for fused speech and the influence of this factor on the quality of synthesized speech on the basis of phonemes are considered. It is proposed to ensure the quality of synthesized speech beginning and ending phonemes at the segmentation set in the transition implementation of a signal through zero and in the synthesis of speech-like signals to use the spline function at the boundaries of segments phonemes.